DOP85 Corticosteroid-free efficacy and safety outcomes in patients receiving tofacitinib in the OCTAVE Sustain maintenance study. (27th May 2021) - Vavricka, S R; Greuter, T; Cohen, B L; Reinisch, W; Steinwurz, F; Fellmann, M; Guo, X; Lawendy, N; Paulissen, J; Peyrin-Biroulet, L
Abstract: Background: Tofacitinib is an oral, small molecule JAK inhibitor for the treatment of ulcerative colitis. Here, we report corticosteroid-free efficacy and safety among patients (pts) who received oral corticosteroids at baseline of the maintenance study (OCTAVE Sustain). Methods: Pts with clinical response following OCTAVE Induction 1&2 who were re-randomised to receive placebo or tofacitinib 5 or 10 mg twice daily (BID) in OCTAVE Sustain, and who were receiving oral corticosteroids at baseline of OCTAVE Sustain, were included. Corticosteroid tapering was mandatory at the beginning of OCTAVE Sustain. Steroid-free (not requiring any treatment with corticosteroids for ≥4 weeks prior to the visit) rates of remission, endoscopic improvement and clinical response were assessed at Week 24 and/or Week 52. The association between baseline characteristics and steroid-free efficacy outcomes was evaluated using logistic regression. Safety outcomes were stratified by tofacitinib dose and steroid-free remission status. Results: Of 593 pts entering OCTAVE Sustain, 289 had oral corticosteroid use at baseline. Of these, 101 (34.9%) received placebo and 188 received tofacitinib (101 [34.9%] 5 mg BID; 87 [30.1%] 10 mg BID) in OCTAVE Sustain. Among pts receiving oral corticosteroids on Day 1 of OCTAVE Sustain, the mean dose (mg/day [standard deviation], prednisone equivalent) received was 15.8 (6.2), 14.9 (6.2) and 14.4 (6.0) in the placebo, tofacitinib 5 mg BID and tofacitinib 10 mg BID groups, respectively. At Week 24 or Week 52 of OCTAVE Sustain, there was a significant treatment effect for tofacitinib 5 or 10 mg BID vs placebo for steroid-free efficacy endpoints (Table 1). Prior immunosuppressant failure was associated with lower odds of achieving steroid-free remission at Week 52 of OCTAVE Sustain (odds ratio [OR] 0.47 [95% confidence interval (CI) 0.23, 0.95]), while prior tumour necrosis factor inhibitor (TNFi) failure status only had a limited effect, which was not statistically significant (OR 0.53 [95% CI 0.27, 1.02]). Oral corticosteroid dose received at baseline of OCTAVE Sustain did not affect the likelihood of achieving steroid-free remission at Week 52. Adverse events of special interest were infrequent (Table 2). Discontinuations were numerically higher among pts without steroid-free remission (Table 2). Conclusion: For pts with baseline oral corticosteroid use in OCTAVE Sustain, the odds of achieving steroid-free efficacy endpoints were significantly higher for tofacitinib 5 or 10 mg BID compared with placebo. Prior TNFi failure was not associated with lower odds of achieving steroid-free remission at Week 52. There were no apparent differences in safety by steroid-free remission status. Data interpretation is limited by small pt numbers.